Establishing Seeded Tall Fescue with Covers and Drip Irrigation Methods - Alex P. Bach; Dale J. Bremer; Cathie C. Lavis; Steven J. Keeley; Mu Hong (Kansas Agricultural Experiment Station Research Reports, 2022)
The use of covers may improve establishment of seeded turfgrass but their use in combination with drip irrigation techniques has not been evaluated. We investigated the effects of two cover types and three irrigation methods on establishment of seeded tall fescue turfgrass. For spring seeding of tall fescue[Schedonorus arundinaceus(Schreb.) Dumort.], turf establishment was successful with subsurface drip irrigation (SDI) and aboveground drip irrigation (AGD) in fine textured soil in the transition zone. With SDI, AGD, or sprinkler irrigation, both polyester mesh (Poly) and straw blanket (Straw) covers improved turf establishment in the order of Poly>Straw>No Cover, but turf establishment in Poly and Straw became similar over time. Soil surface temperature averaged higher in Poly (14°C [57°F]) than Straw (9.5°C [49°F]) and No Cover (8.6°C [47.5°F]) during the first 12 days after seeding when covers were installed. Results indicate that covers improved spring establishment of seeded, cool-season turfgrass in a fine-textured soil and in a US transition zone climate by mitigating low temperature extremes and reducing erosion during rainfall. Establishment was similar between drip (SDI and AGD) and sprinkler irrigation, but the use of protective covers is recommended when establishing turfgrass from seed.
Keywords: subsurface drip irrigation; aboveground drip irrigation; polyester mesh; straw blanket; seeded tall fescue; turfgrass establishment